1973
DOI: 10.1002/cpt1973144part2632
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of drugs taken by pregnant women: Drugs that may affect the fetus adversely

Abstract: The epidemiology of drug consumption during pregnancy has been studied retrospectively in 911 randomly selected mothers. The drugs used, the proportions of pregnant women taking them, the duration and timing of drug administration were ascertained. Excluding iron, drugs were prescribed for 82 % of women during pregnancy and the average number of drugs prescribed for these women was 4. Self-medicated drugs were taken by 65% of mothers and the average number of drugs taken by these was 1.5. The proportion of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
4

Year Published

1975
1975
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(32 citation statements)
references
References 12 publications
0
28
0
4
Order By: Relevance
“…To our knowledge, this is the first time that an altera tion of the development of the GBM has been reported after the mother was treated with drugs during gestation [12][13][14]28,39,40], In utero acquired nephrotoxicity, how ever, has been previously demonstrated after aminogly coside administration to the mother [20,21,26,41]. The noted functional and pathological modifications found then were very similar to those observed in adults, i.e.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…To our knowledge, this is the first time that an altera tion of the development of the GBM has been reported after the mother was treated with drugs during gestation [12][13][14]28,39,40], In utero acquired nephrotoxicity, how ever, has been previously demonstrated after aminogly coside administration to the mother [20,21,26,41]. The noted functional and pathological modifications found then were very similar to those observed in adults, i.e.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, the few warnings against the use of aminoglycosides for pregnant women [14] and premature or full-term neonates are based almost exclusively on their potential ototoxicity [15]. Nevertheless, the relationship of gentamicin excre tion to post-conceptual age is well established [16], and it is known that infants treated with recommended dosages 1 A preliminary account of this work was published as an abstract in ref.…”
mentioning
confidence: 99%
“…A moderate concentration of alco hol in instrumented pregnant ewes (200 mg/ 100 ml = 44 mM) produced a reduction in myocardial contractility in fetuses as as sessed by systolic time interval changes [7], It has been suggested that ethanol may cause direct and deleterious effects on hu man fetal myocardial cell physiology [7]; however, evidence in support of this is want ing. We believe that this merits study since social drinking is not uncommon among pregnant women [3,8] and may be a pre ventable risk to the fetus. Avoidance of so cial drinking during pregnancy may be advo cated but the justification for this caveat is arguable at present.…”
Section: Introductionmentioning
confidence: 99%
“…Two reports indicate that as many as 16 to 41% of fetuses (8 weeks' gestation to delivery) are exposed to antibiotics for treatment of an infection occurring during pregnancy (6,7). These infections may involve the gravida alone, all or part of the intrauterine contents, or both the mother and fetus.…”
mentioning
confidence: 99%